Site-directed attachment of photoexcitable spin labels for light-induced pulsed dipolar spectroscopy. Issue 93 (7th November 2020) - Williams, Lara; Tischlik, Sonja; Scherer, Andreas; Fischer, Jörg Wolfram Anselm; Drescher, Malte
Abstract : We report the first example of EPR distance determination using photoexcitable spin labels site-selectively attached via click or thiol chemistry. Abstract : Photoexcited triplet states are gaining popularity as spin labels in pulsed electron paramagnetic resonance (EPR) spectroscopy. Here, we demonstrate that the fluorophores Eosin Y, Rose Bengal and Atto Thio12 are suitable markers for distance determination by laser-induced magnetic dipole (LaserIMD) spectroscopy in proteins that lack an intrinsic photoexcitable center.